2009
DOI: 10.1016/j.aap.2009.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Illegal pedestrian crossing at signalised intersections: Incidence and relative risk

Abstract: Illegal pedestrian behaviour is common and is reported as a factor in many pedestrian crashes. Since walking is being promoted for its health and environmental benefits, minimisation of its associated risks is of interest. The risk associated with illegal road crossing is unclear, and better information would assist in setting a rationale for enforcement and priorities for public education. An observation survey of pedestrian behaviour was conducted at signalised intersections in the Brisbane CBD (Queensland, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(65 citation statements)
references
References 8 publications
2
60
0
2
Order By: Relevance
“…While pedestrians seem to be unaware of the increased risk associated with non-compliance, King et al (2009) found that it, in fact, increased their risk eight times. Illegal pedestrian behaviour has been shown to be the main cause of pedestrian crashes, but still non-compliance rate has continued to increase [3,5]. Harrel's study [33] also concluded that pedestrians' level of cautiousness is significantly influenced by the volume of traffic, which he attributed to the diffusion of responsibility.…”
Section: Walkability and The Evaluation Of Pedestrian Crossings: A Rementioning
confidence: 99%
See 3 more Smart Citations
“…While pedestrians seem to be unaware of the increased risk associated with non-compliance, King et al (2009) found that it, in fact, increased their risk eight times. Illegal pedestrian behaviour has been shown to be the main cause of pedestrian crashes, but still non-compliance rate has continued to increase [3,5]. Harrel's study [33] also concluded that pedestrians' level of cautiousness is significantly influenced by the volume of traffic, which he attributed to the diffusion of responsibility.…”
Section: Walkability and The Evaluation Of Pedestrian Crossings: A Rementioning
confidence: 99%
“…However, certain operational-level design such as the long waiting time (red traffic signal phase) encourages risk-taking and illegal behaviour among pedestrians at crossings [4]. A survey conducted along Brisbane's street intersections confirmed that a high percentage of pedestrians exhibited illegal behaviour, such as 'crossing against the lights' and 'close to the lights' [3]. While pedestrians seem to be unaware of the increased risk associated with non-compliance, King et al (2009) found that it, in fact, increased their risk eight times.…”
Section: Walkability and The Evaluation Of Pedestrian Crossings: A Rementioning
confidence: 99%
See 2 more Smart Citations
“…Based on the gap acceptance theory researchers have developed mathematical models to represent the gap acceptance behavior of pedestrian with the help of pedestrian demographic characteristics such as gender and age [5], types of vehicle and waiting time [6], effect of rolling gap [7], effect of parked vehicles [8], non-compliant road crossing behavior at midblock locations [9], [10] and non-compliant road crossing behavior at signalized intersection [11].…”
Section: Literature Reviewmentioning
confidence: 99%